Mathematics
ToriKirlin
31

Solve for x. 6(x – 1) = 9(x + 2) x = –8 x = –3 x = 3 x = 8

+3
(2) Answers
wonkey

so first multiply: 6x -6 = 9x + 18 then we "move the numbers ": 6x-9x= 18 +6 the positive and negative signs will change. anyways, now combine the like terms: -3x= 24 now we divide 3 from both sides in order to isolate x: -3÷3x= 24÷3 -x = 8 noq divide the negative from both sides: x= -8

dimasaleh101

6(x – 1) = 9(x + 2) 6x - 6 = 9x + 18 9x - 6x = -6 - 18 3x = -24 x = -24/3 x = -8 In short, Your Answer would be -8 [ Option A ] Hope this helps!

Add answer